PENGARUH KARAKTERISTIK KOMITE AUDIT PADA PRAKTIK MANAJEMEN LABA RIIL (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI tahun 2014-2016) - Qorry Eka Pertiwi; Herry Laksito (Diponegoro Journal of Accounting, 2019)
This study aims to investigated the influence of audit committee characteristics in relation to real earnings management. Audit committee characteristics in this research refers to research conducted by Sun and Lan (2014).  Independent variabel used in this study are accounting financial expertise, board of tenure, additional boards, and committee size. Dependent variable in this study is real earnings management. This study used three control variables, include size, market to book ratio, and return on assets. This study used secondary data. The population consists of manufacture companies listed on Indonesia Stock Exchange during 2014 until 2016. Sampling method used is purposive sampling. The samples were 44 companies. Analysis test using multiple regression analysis.The results of this study show that there is significant relationship between board of tenure, additional boards, and committee size to real earnings management. But, there is no significant relationship between accounting financial expertise to real earnings management.